2019
DOI: 10.17222/mit.2018.156
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional errors in selective laser melting products related to different orientations and processing parameters

Abstract: This research has investigated the changes of dimensions with changes of the Energy Density (ED), processing parameters and build up direction wise of Ti-6Al-4V alloy products manufactured by the Selective Laser Melting (SLM) process. The selected processing parameters were laser power, scanning speed, and hatch spacing in several combinations, keeping the layer thickness constant during all three steps of the studies. Four orientations have been considered for a specimen to build up in different directions fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The second option is to control the laser/beam power, scanning speed, scanning type, and layer thickness using KBS so that we can obtain the desired products [33]. It could also be possible to control the metal bath and thermal shrinkage by increasing or decreasing the thermal conductivity [12], which can be controlled by increasing or decreasing the support conditions to obtain the desired dimensions [24].…”
Section: Product Quality Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…The second option is to control the laser/beam power, scanning speed, scanning type, and layer thickness using KBS so that we can obtain the desired products [33]. It could also be possible to control the metal bath and thermal shrinkage by increasing or decreasing the thermal conductivity [12], which can be controlled by increasing or decreasing the support conditions to obtain the desired dimensions [24].…”
Section: Product Quality Controlmentioning
confidence: 99%
“…The problem of dimensions is one of the major problems with an AM product [12]. The product dimensions are only slightly different from those of the model CAD.…”
Section: Introductionmentioning
confidence: 99%
“…Xia et al (2018) had such results that Co–Cr cubic specimens built with a 550-mm/s scan speed and 115-W laser power had more minor height errors than those built with other levels of these two process parameters. Pal et al (2019) concluded that the linear energy density, or the ratio of laser power to scan speed and hatch space, affects the side and height dimensional errors of Ti–6Al–4V cubic specimens. It is found out of practice that the distortion of maxillary RPD frameworks is more common than that of mandibular RPD frameworks.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of laser process parameters on the accuracy of RPD frameworks have not been thoroughly investigated. Laser process parameters indeed affect not merely the dimensional accuracy of parts (Vandenbroucke and Kruth, 2007; Pal et al , 2019) but the warpage and distortion of parts. Xia et al (2018) had such results that Co–Cr cubic specimens built with a 550-mm/s scan speed and 115-W laser power had more minor height errors than those built with other levels of these two process parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been carried out on the properties of products made with the powder bed additive manufacturing processes, in particular the selective laser melting (SLM) process [1][2][3]. However, these investigations were based on employing different processing parameters [4][5][6], scanning strategies [7], and different build-up directions due to different angular orientations of the part [8,9].…”
Section: Introductionmentioning
confidence: 99%